Pricing the term structure with linear regressions - Tobias Adrian; Emanuel Moench (Federal Reserve Bank of New York, 2008)
We show how to price the time series and cross section of zero coupon bonds via ordinary least squares regressions. Our approach allows computationally fast estimation of term structure models with a large number of pricing factors. Even though we do not impose cross-equation restrictions in the estimation, we show that our return regressions generate a term structure of interest rates with small pricing errors compared to commonly reported specifications, both in and out-of-sample.
Keywords: G10; G12; 330; Term structure of interest rates; fama-macbeth regressions